Longitudinal Sampling of the Rainbow Trout (Oncorhynchus mykiss) Microbiome Reveals Effects of Dietary Cecropin A and Yersinia ruckeri Infection - Sibinga, Nathaniel A.; Lee, Min-Ting; Johnson, Elizabeth L.; Selvaraj, Vimal; Marquis, Hélène (Frontiers in Marine Science, 2022)
The aquaculture industry faces growing pressure to reduce the use of antibiotics for control of bacterial diseases. In this study we tested the effectiveness of dietary cecropin A, an insect-derived antimicrobial peptide, at preventing mortality and reducing incidence of carrier status in rainbow trout (Oncorhynchus mykiss) challenged by immersion with Yersinia ruckeri. Additionally, we conducted longitudinal analyses of microbiome changes to elucidate effects of both cecropin A and bacterial infection. An in vitro experiment indicated that Y. ruckeri is susceptible to cecropin A. However, dietary cecropin A did not improve the survival of fish challenged with Y. ruckeri, nor did it decrease the persistence of Y. ruckeri in the intestine of fish that survived infection. Moreover, levels of intestinal Y. ruckeri as measured by qPCR suggested that cecropin A may have negatively impacted the ability of fish to resist colonization by this bacterial pathogen. Concomitantly with the survival experiments, the microbiomes of challenged and mock-challenged fish were sampled at days 0, 3, 8, and 30. The microbiomes were in general dominated by Mycoplasma sp. at days 0, 3 and 8, independent of diet, and whether fish had been challenged or mock-challenged. At day 30, the microbiomes of mock-challenged fish fed the +cecropin diet were characterized by lower internal (alpha) diversity (p<.01), greater relative abundance of Mycoplasma sp., and a decrease in gram-negative taxa, when compared to the microbiomes of fish fed the control diet. The opposite was observed in the microbiome of challenged fish. Lastly, correlation analysis of amplicon sequence variants (ASVs) revealed a negative correlation between the presence of Y. ruckeri and seven ASVs, including Mycoplasma sp., suggesting possible beneficial effects of these taxa. In addition, six ASVs were positively correlated to Y. ruckeri, including Flavobacterium succinicans – a known opportunistic fish pathogen. In conclusion, this study revealed that dietary cecropin A was bioactive and exerted significant effects on the microbiome but did not improve fish resistance to infection by Y. ruckeri. Based on our observations and other published results, it appears that high relative abundance of Mycoplasma sp. correlates with higher resistance to intestinal colonization by bacterial pathogens.